2014
DOI: 10.1002/hbm.22710
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical intelligence: Caudate volume predicts IQ in healthy adults

Abstract: This study examined the association between size of the caudate nuclei and intelligence. Based on the central role of the caudate in learning, as well as neuroimaging studies linking greater caudate volume to better attentional function, verbal ability, and dopamine receptor availability, we hypothesized the existence of a positive association between intelligence and caudate volume in three large independent samples of healthy adults (total N = 517). Regression of IQ onto bilateral caudate volume controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 48 publications
11
40
0
Order By: Relevance
“…Finally, we opted to include subcortical volumes in a post-hoc (non-pre-registered) analysis. Consistent with prior reports (Basten et al, 2015;Grazioplene et al, 2015;Rhein et al, 2014), we found significant bilateral associations with the caudate, though these were not significantly larger than the magnitudes found for the majority of subcortical structures. In fact, thalamic volume was substantially more strongly related to general intelligence (≥1.5 times as large) than any other subcortical structure (r for left and right = 0.255 and 0.251).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, we opted to include subcortical volumes in a post-hoc (non-pre-registered) analysis. Consistent with prior reports (Basten et al, 2015;Grazioplene et al, 2015;Rhein et al, 2014), we found significant bilateral associations with the caudate, though these were not significantly larger than the magnitudes found for the majority of subcortical structures. In fact, thalamic volume was substantially more strongly related to general intelligence (≥1.5 times as large) than any other subcortical structure (r for left and right = 0.255 and 0.251).…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, we hypothesised that thalamic and association fibres, plus forceps minor will show the statistically largest associations with general intelligence. The additional use of subcortical volumes was an addition to our preregistered plan; subcortical structure did not figure largely in the P-FIT (Jung & Haier., 2007), though more recent work has reported associations between intelligence and overall subcortical volume (Ritchie et al, 2015), caudate (Basten et al, 2015;Grazioplene et al, 2015;Rhein et al, 2014), hippocampal (Valdés Hernández et al, 2017) and thalamic volume (Bohlken et al, 2014).…”
Section: Associations Between G and Regional Brain Mri Measuresmentioning
confidence: 99%
“…Syntactic processing, likewise, appears to involve the left caudate and putamen, as well as the globus pallidus (Friederici et al, 1999;Kotz et al, 2003;Friederici et al, 2003b,a;Newman et al, 2010). And, most directly related to the findings here, morphological measures of the basal ganglia have been associated with IQ (MacDonald et al, 2000;Isaacs et al, 2008;Grazioplene et al, 2015), with some specificity of the core relation being between the caudate and VIQ (Isaacs et al, 2008;Grazioplene et al, 2015).…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, it seems likely that including the intensity contrast at the subcortical gray-white boundaries might capture additional aspects of brain maturation related to cognitive development. Subcortical regions play important roles in cognitive, affective, and social functions (Johnson, 2005;Utter and Basso, 2008;van Schouwenburg et al, 2010;Fischi-Gómez et al, 2014;Humphries and Prescott, 2010;Grazioplene et al, 2015;Bohlken et al, 2016;Guo et al, 2006;Isaacs et al, 2008), and subcortical abnormalities have been associated with various psychiatric disorders (Rimol et al, 2010;Hartberg et al, 2011;Cerliani et al, 2015;Hibar et al, 2016;Hoogman et al, 2017).…”
mentioning
confidence: 99%
“…A clear candidate for one of the neuroanatomical bases of cognitive ageing is brain volume. Measures of total brain volume, as well as the volumes of specific tissue types, have consistently been shown to correlate with cognitive ability level throughout adulthood [Arvanitakis et al, in press;Grazioplene et al, 2015;Pietschnig et al, 2014], and changes in brain tissue volumes accompany normal ageing, with healthy tissue volumes declining and white matter hyperintensity (WMH) volumes increasing [Fjell and Walhovd, 2010;Fleischman et al, 2014;Prins and Scheltens, 2015]. In a two-wave longitudinal study with a large narrow-age cohort, we investigate the associations between changes in important domains of cognitive ability and in total brain volume, grey matter volume, normal-appearing white matter volume, and volume of WMH during the eighth decade of life.…”
Section: Introductionmentioning
confidence: 99%